BIODEGRADASI SENYAWA ORGANIK DAN AMONIUM DALAM LIMBAH CAIR INDUSTRI MINYAK KELAPA SAWIT DENGAN SISTEM PERTUMBUHAN MIKROORGANISMA TERLEKAT - Dwi Agustiyani; Hartati Imamuddin (BERITA BIOLOGI, 2000)
Efficiency of biodegradation of organic carbon and ammonium of sawit palm oil industry wastewater was investigated by using batch reactor with fluidized porous support particles.Two bioreactors, each had an effective volume of 3.0 L, were operated in parallel. Bioreactor-l is a batch reactor with fluidized porous support particles and bioreactor-ll is a suspended growth reactor.The wastewater consisting of 1500-2000 mg/L COD and 50-60 mg/L nitrogen was fed by fill and draw mode with one cycle per day,where 1.5 L treated water was drawn before adding the new wastewater.Efficiency of COD degradation and nitrification were calculated by measuring concentration of COD, ammonium-N, nitrite-N and nitrate-N.The experimental results showed that efficiency of COD degradation and nitrification tend to be higher in the bioreactor-l than in the bioreactor II.The highest efficiency of COD degradation in the reactor-l was 83.7% and in the bioreactor-ll was 63.44 %.The highest efficiency of nitrification in the bioreactor-l and bioreactor-ll was 76.72% and 56%, respectively.Ammonium removal occurred in the bioreactor might not only by biological nitrification, but also by other phisical or chemical processes.